Cardiopulmonary bypass: development of John Gibbon's heart-lung machine - Passaroni, Andréia Cristina; Silva, Marcos Augusto de Moraes [UNESP]; Yoshida, Winston Bonetti [UNESP] (Sociedade Brasileira de Cirurgia Cardiovascular, 2015)
To provide a brief review of the development of cardiopulmonary bypass. A review of the literature on the development of extracorporeal circulation techniques, their essential role in cardiovascular surgery, and the complications associated with their use, including hemolysis and inflammation. The advancement of extracorporeal circulation techniques has played an essential role in minimizing the complications of cardiopulmonary bypass, which can range from various degrees of tissue injury to multiple organ dysfunction syndrome. Investigators have long researched the ways in which cardiopulmonary bypass may insult the human body. Potential solutions arose and laid the groundwork for development of safer postoperative care strategies. Steady progress has been made in cardiopulmonary bypass in the decades since it was first conceived of by Gibbon. Despite the constant evolution of cardiopulmonary bypass techniques and attempts to minimize their complications, it is still essential that clinicians respect the particularities of each patient's physiological function.